Distributed Birefringence Measurement of a Polarization-Maintaining Fiber With an Extended Range Based on an Enhanced Brillouin Dynamic Grating - Taofei Jiang; Dengwang Zhou; Meng Xia; Lei Teng; Dexin Ba; Yongkang Dong (IEEE Photonics Journal)
A distributed birefringence measurement of a polarization-maintaining fiber (PMF) can be realized by using a Brillouin dynamic grating (BDG). However, the pump depletion decreases the intensity of the BDG along the PMF and limits the measurement range to a few hundred meters. We demonstrate a distributed birefringence measurement of the PMF with an extended range to 3030 m based on an enhanced BDG with an 18.5-ns pump-1 pulse, frequency-upshifted continuous-wave pump-2, and 4-ns read pulse (spatial resolution: 40 cm). The enhanced BDG is promising to characterize the design of a fiber coil to improve the fiber optic gyroscope performance.